Different internal metabolites trigger the induction of glycolytic gene expression in Saccharomyces cerevisiae. - Müller, S (1995)
In the yeast Saccharomyces cerevisiae, the sugar-induced expression of various genes coding for glycolytic enzymes is triggered by increases in the concentrations of different internal metabolites. Here, we show that the induction of the glycolytic isoenzyme enolase 2 is strictly dependent on the abilities of different mutant strains to increase the level of glucose-6-phosphate after the addition of sugars. In contrast, the induction of alcohol dehydrogenase I is dependent on increasing concentrations of metabolites in the late stages of glycolysis.